Addition of in-situ reduced amidinato-methylaluminium chloride to acetylenes - Chlupatý, Tomáš; Turek, J.; De Proft, F.; Růžičková, Zdeňka; Růžička, Aleš (Royal Society of Chemistry, 2015)
Two ethylene-bridged methylaluminium amidinates and one aluminium amidinate containing three terminal trimethylstannyl-ethynyl groups interconnected by π-coordinated potassium ions were prepared in situ. The re-oxidation of the ethylene-bridged compound by iodine followed by further reduction using the same activation procedure demonstrated the versatility of the approach. The reactivity of an ethylene-bridged methylaluminum amidinate towards HCl was examined to demonstrate the building block concept. DFT calculations were performed to gain insight into the mechanism of the in situ activation of diphenylacetylene.